Análisis de la aplicación de la inteligencia artificial para la detección de amenazas en redes de datos - Riofrío Aguilar, Luis Eduardo (2024)
In this current study, the analysis of the use of artificial intelligence in data network security was addressed from different scenarios, from both defensive and offensive point of view, and how these tools are leveraged in each of these areas. Thus, we will differentiate the use of these artificial intelligence tools into two teams: the blue team (defensive) and the red team (offensive); and according to the nature of their functions, which tools currently are available and could use to achieve their objectives. To conclude this analysis, recreations of certain scenarios were carried out demonstrating how defensive and offensive tools are used, allowing us to observe the advantages and disadvantages we face regarding to AI. Keywords: Artificial Intelligence, Cybersecurity, Cyberattacks